Relationship between Health Workers’ Body Mass Index, Emotional Eating, And Uncontrolled Eating - Ismail , Moamen Abdelfadil; ALHERZ, EMAN MOHAMMED; Alsaffar, Zainab Saud; AlMutairi , Rawan Turki; AlHassan , Ghadeer Hussain; Hussein, Fatima Abdullah; Altulaihi, Mounira; Aljohani , Ahlam Awad; Al-Rashidi, Nasser Saad; Asiri, Bahni Mohammad; bahkali, Mousa ahmed; Dawshah, Marwan Abdulaziz Abu (Journal of Ecohumanism, 2024)
Background: Obesity and overweight are significant public health concerns globally, with healthcare professionals being particularly vulnerable due to high job demands and stress. The relationship between body mass index (BMI), job stress, and eating behaviors remains underexplored in this population, despite evidence linking workplace stress to unhealthy eating habits and weight gain. Methods: This study, conducted over three months , assessed the relationship between BMI, job stress, and eating behaviors among 400 male and female healthcare professionals. Participants were classified into normal, overweight, and obese BMI categories based on measured weight and height. Data were collected using the Brief Job Stress Questionnaire and the Adult Eating Behaviour Questionnaire (AEBQ). Statistical analysis, including descriptive statistics and Spearman’s rank correlation, was performed using SPSS version 28, with a significance threshold of p ≤ 0.05. Results: Among the participants, 230 had normal BMI, 110 were overweight, and 60 were classified as obese (class 1 and class 2). Physiotherapists reported the highest levels of job stress, particularly in the normal BMI category, while dental professionals experienced the least. Eating behaviors were elevated in 260 participants, with mean AEBQ scores varying across BMI categories. Despite the high prevalence of job stress and altered eating behaviors, the correlation between BMI, job stress, and eating behavior was weak and not statistically significant. Conclusion: The study highlights that while job stress and unhealthy eating behaviors are prevalent among healthcare professionals, their direct correlation with BMI remains inconclusive. Lifestyle factors such as physical activity and dietary habits may play a more critical role in influencing BMI, underscoring the need for targeted interventions to promote healthier lifestyles in this population.